IMPLEMENTASIiKEBIJAKAN PELAYANAN TERPADU SATU PINTU DI KOTA KENDARI PROVINSIiSULAWESI TENGGARA (Studi. Kasus di Dinas Penanaman. Modal dan Pelayanan TerpaduiSatu Pintu) - Agung Nurrahman; Muh. Marzab Dasilva (Institut Pemerintahan Dalam Negeri, 2020)
The focus of the study discusses the implementation of a one-stop integrated service City policy in Kendari, Southeast Sulawesi Province. The purpose of this research is to find out and analyze the implementation of a one-stop integrated service policy in Kendari City. The concept used is the theory of policy implementation presented by George Edwards III that the dimensions of policy implementation are: 1) communication, 2) resources, 3) disposition and 4) bureaucratic structure. The method used is descriptive qualitative with an inductive approach. The models used in analyzing the data through data reduction, the data presentation, and drawing Conclusions. Based on the results of research that the Office of Investment and Integrated Services of the One Door of the City of Kendari in the implementation of the One Door Integrated Services Policy can be Categorized as not good yet. This can be seen from the four dimensions of research, there are 3 (three) dimensions that are not good items, namely the dimensions of Communication, Disposition, and Bureaucratic Structure. Keywords: Implementation, Policy, Public Services, One Stop Integrated Services